Meningkatkan Keaktifan Belajar Dan Hasil Belajar Peserta Didik Mata Pelajaran Akidah Akhlak Melalui Penerapan Model Numbered Heads Together (NHT) Pada Peserta Didik Kelas II Semester Ganjil Mi Ma’arif Brajan - Partinah Partinah (THE JOER: Journal Of Education Research, 2022)
Based on the analysis of the results of daily tests or midterm and semester tests, it is known that the learning outcomes of students in class 2 MI Ma'arif Brajan Kulon Progo odd semester of 2021 in the moral aqeedah subject are low. It is proven that there are students who score below the KKM, there are 50%, students who score the same as the KKM, there are 35% and students who score above the KKM, there are 15%. From the analysis of the causes of the problem, the effort that is expected to improve the learning outcomes of students in grade 2 MI Ma'arif Brajan Kulon Progo odd semester of 2021 in the Akidah Akhlak subject is the application of the right model. Through this research, researchers want to increase the activity and learning outcomes of students in class 2 MI Ma'arif Brajan Kulon Progo odd semester of 2021 in the subject of aqidah morals through the application of the Numbered Heads Together (NHT) learning model. This research is a Classroom Action Research (CAR) with a spiral model from Kemmis and Taggart which consists of several action cycles. The results showed that the activity from the initial conditions, cycle 1 and cycle 2 continued to increase. In the initial conditions for cycle 1 and cycle 2, the percentage of students whose activity was in the low category continued to decrease, namely 75% - 59% - 4%. While the moderate category is from 20% - 26% - 52%. While the high category is from 5% - 14% - 42%. Meanwhile, student learning outcomes experienced an increase after the action was taken. The percentage of students who have not completed has decreased from cycle 1 to cycle 2 (from 72% to 0%). The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 28% to 100%).